EVALUATION OF THE MICROBIOLOGICAL QUALITY AND PUBLIC HEALTH RISK OF COMMONLY USED COSMETICS BRANDS IN KADUNA STATE, NIGERIA - Shitu, Sabiu; Aliyu, M. Y.; Abubakar, A. A. (FUDMA JOURNAL OF SCIENCES, 2022)
Cosmetics are substances that are used to enhance the physical aspect of humans. Because it can result in both product and financial losses, the cosmetics industry takes microbial contamination very seriously. The objective of the present investigation was to assess the microbiological quality and risk to public health of commonly used cosmetics in Kaduna State. A sterile swab was used to collect forty (40) distinct used cosmetics. Using standard protocol, the samples were inoculated onto nutrient agar, macConkey agar, and sabourad dextrose agar for the isolation and identification of bacteria and fungi. The prevalence of the isolates revealed that Staphylococcus aureus (35.3%) and E. coli (29.4%) were present in the samples, while Bacillus and Micrococcus sp. each accounted for 4.8%. Aspergillus and Rhizopus sp. had the greatest incidence rates, at 47.6% and 23.8%, respectively, while Botriytis and Alternaria account for 4.8% each. The percentage occurrence of both bacterial and fungal isolates was statistically significant, P 0.05, among the brands of cosmetics analysed. The percentage of bacteria and fungi found in the study clearly indicates the degree to which the cosmetics were contaminated during production, packaging, or use. Numerous bacteria and fungi, including Escherichia coli, Staphylococcus aureus, Bacillus sp., Micrococcus sp., Pseudomonas aeruginosa, Rhizopus, Penicillium, Fusarium, Aspergillus, Botriytis, and Alternaria species, were found to be contaminating a variety of cosmetic products that were analysed. Microbes may contaminate personal care products during production due to the handling of raw materials, or after repeated use by consumers. The necessity